Hyperergic Aspiration Pneumonitis (Mendelson Syndrome) - Ye. M. Shifman (Общая реаниматология)
This paper gives basic data on the problem of hyperergic aspiration pneumonitis (Mendelson’s syndrome) in obstetric anes-thesiological practice. It describes changes in the gastrointestinal tract during pregnancy and labor. The pathology and mechanisms of aspiration are considered. The existing preventive methods are analyzed in detail. The new regulations of preopera-tive preparation of patients for planned anesthesia at cesarean section are presented.